login
a(n) = (((n^n)^n)/(n^n)/n)-((n^n)/n)-n.
0

%I #9 Mar 30 2012 19:00:47

%S -1,-2,231,4194236,19073486327495,36845653286788892975514,

%T 44567640326363195900190045974450351,

%U 46768052394588893382517914646921056628989839278072,56392087339601733413306017749077372989860250021295987473736339410479

%N a(n) = (((n^n)^n)/(n^n)/n)-((n^n)/n)-n.

%p a:= n-> (((n^n)^n)/(n^n)/n)-((n^n)/n)-n:

%p seq (a(n), n=1..9);

%K sign

%O 1,2

%A _Ben Branman_, Dec 01 2007

%E Corrected and extended by _Alois P. Heinz_, Jan 17 2011